Battery charging stations for home lighting in Mekong region countries. (April 2015) - Pode, Ramchandra
Abstract: The role of energy services in social and economical developments is well recognized. However, rural populations in developing countries are deprived of affordable and reliable energy services. Batteries are considered as potential and relatively cheap source of power for home lighting in remote rural areas. These can be charged at affordable fee at Battery Charging Stations (BCSs) with a diesel generator and/or solar BCSs. Diesel generators are emitting CO2 green house gas and contributing to environmental pollution. While, the Solar Battery Charging Stations (SBCSs) with battery backup (i) address the issue of environmental pollution, (ii) reduce the production and use of fossil fuels, and (iii) also prevent the energy intermittency in rainy or cloudy days. In Mekong region countries, most of the existing BCSs are powered by diesel generators. Diesel power generators for battery charging are very popular and affordable options for the low income populations. However, the solar BCS systems for battery charging are also introduced during the last decade. In the present review paper, the BCS stations providing electricity services to remote rural households in Mekong region countries, in particular Cambodia, Lao PDR and Myanmar, are discussed. It is argued that the BCS systems (pre grid electrification schemes) to power remote houses are relevant for the rural electrification where either grid or mini-grid sites are far away or take decades to reach the grid electricity.